Problem-Based Learning Assisted by Canva to Improve Exposition Text Writing Skills - Arum Wiarsih; Setyawan Pujiono (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to improve students’ ability in writing exposition texts through the implementation of the Problem Based Learning (PBL) model assisted by Canva-based interactive media. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 36 tenth-grade students of the Culinary program at SMK Negeri 1 Maja. Data were collected through writing tests, observation, and documentation, and analyzed using descriptive quantitative techniques.The results show a significant improvement in students’ writing skills. The average score increased from 60 in the pre-cycle to 72 in Cycle I and 85 in Cycle II. The findings indicate that the implementation of PBL assisted by Canva effectively enhances students’ ability to organize ideas, develop arguments, and apply appropriate language features in writing exposition texts.In conclusion, the integration of Problem Based Learning and Canva-based interactive media improves students’ writing skills and creates a more active, interactive, and student-centered learning process.